Strengthening Islamic Finance through the Merger of Two Sharia Banking Entities - Junaedi, Edy; Maulana, Irwan (Yayasan Mitra Peduli Indonesia, 2025)
Acquisitions are critical for banks seeking to increase their market presence in the evolving Islamic financial landscape. This study examines the strategic potential of Bank B Syariah's acquisition of Bank V Syariah. Then this study focuses on market expansion, product innovation, and operational efficiency. This study uses a mixed method. Data are derived from financial reports, industry trends, and regulations of the Financial Services Authority in Indonesia. The results show that the acquisition expanded Bank B Syariah's network by 25%, added 15 new Sharia-compliant products, and increased efficiency through economies of scale. In addition, there are significant challenges: post-merger risk management, aligning the Islamic compliance framework, and integrating different technology infrastructures. As an implication, three main strategies must be carried out: a gradual consolidation process to align organizational culture, strengthening Sharia governance through an independent supervisory board, and adopting digital technology to support integration and improve customer service. This study contributes to understanding the complexity of mergers in Islamic banking.